Use of Banana Peel as a Raw Material for Banana Peel Nugget on a Small Industrial Scale - Yosefina Nunila Mbue; Wahyu Mushollaeni; Atina Rahmawati (Indonesian Journal of Food Technology, 2023)
The aim of this research is to obtain the best treatment from the use of various types of banana peels with flour and sago formulations in making banana peel nuggets and to find out the business feasibility analysis of making banana peel nuggets resulting from the best treatment. This research was designed using a Randomized Block Design (RAK) with two factors, namely the type of banana peel and the concentration of wheat flour and sago flour. Factor I: type of banana peel: 50% mas banana, 50% Ambon banana, 50% king banana, 50% milk banana, and 50% kepok banana. Factor II: concentration of wheat flour and sago flour: wheat (40%, 30%) and sago (10% and 20%). The parameters observed in this research were crude fiber content, water content, and liking test (aroma, color and texture). Statistical analysis was carried out using Analysis of variance ANOVA. Based on the research results, the addition of flour and sago concentrations did not have a significant effect on the fiber content, water content and organoleptic content of banana peel nuggets. The type of banana peel and the concentration of wheat and sago received the best treatment with Yield Value (NH), namely in the P5T1 treatment with 50% kepok banana peel treatment with 40% wheat flour and 10% sago flour with a value of 0.76. Banana peel nuggets contain 3.18% fiber content, 43.50% water content, 4.48% aroma preference, 4.35% color preference and 4.53% texture preference. The results of the business feasibility analysis obtained a Ratio (R/C) value of 1.55, so it was stated that the production of banana peel nuggets was feasible.